EFL Teachers' Beliefs and ICT Integration Practices During Distance Learning: Employing Replacement, Amplification, and Transformation Framework - Anggi Purwa Lestarina; Joko Nurkamto Nurkamto; Ngadiso Ngadiso Ngadiso (Register Journal, 2022)
Technology is successfully integrated when technology makes learning effective, efficient, and creative. It cannot be denied that technology positively contributes to teaching and learning. Moreover, in the current pandemic conditions where the learning process must be carried out remotely, technology helps this teaching and learning process more accessible. The objective of the study is to see the EFL teachers’ beliefs and ICT integration practices during distance learning. This study investigates teachers' beliefs of ICT integration based on the current theory and situation. The researchers used a qualitative approach in this case study; three EFL teachers were interviewed and observed. The finding of the study is all EFL teachers had positive beliefs about ICT use for teaching and learning and student-centered belief orientation for pedagogical belief. One of three had low-self efficacy to utilize ICT. ICT was integrated for effective and efficient learning, which means teachers' level of ICT integration was Amplification based on the RAT (Replacement, Amplification, and Transformation) framework. However, overall, teachers' beliefs orientation were positive belief about ICT integration, high self-efficacy belief, student-centered belief. Still, they could not reach the high level of ICT integration linked to creativity in teaching. They also faced some barriers in integrating ICT, such as students' engagement and the learning in the distance still incomplete. They missed the motivation or stimulation stage for their students and the students' learning process was lack of speaking and listening enhancement activities. Additional research should address more people as data objects to corroborate research results.Keywords: ICT integration, RAT framework, Teachers' Beliefs, Self-efficacy beliefs, Pedagogical beliefs